2015
DOI: 10.1016/j.bpj.2015.09.005
|View full text |Cite|
|
Sign up to set email alerts
|

Electrostatic Similarity Analysis of Human β-Defensin Binding in the Melanocortin System

Abstract: The β-defensins are a class of small cationic proteins that serve as components of numerous systems in vertebrate biology, including the immune and melanocortin systems. Human β-defensin 3 (HBD3), which is produced in the skin, has been found to bind to melanocortin receptors 1 and 4 through complementary electrostatics, a unique mechanism of ligand-receptor interaction. This finding indicates that electrostatics alone, and not specific amino acid contact points, could be sufficient for function in this ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…This may be due to complementary electrostatic interaction between the cationic peptide and receptors with anionic regions. HBD3, the most highly charged β-defensin (charge of +11) has been demonstrated to be a neutral antagonist, through charge based interaction with melanocortin receptor 1 and 4 (82). In dogs, a three base pair deletion in the canine orthologue of HBD3 results in an increase in the level of expression, which then allows this peptide to promiscuously bind the melanocortin receptor 1 (MC1R)-resulting in dogs with black, rather than agouti, fur (83).…”
Section: Receptor Neutral Antagonismmentioning
confidence: 99%
“…This may be due to complementary electrostatic interaction between the cationic peptide and receptors with anionic regions. HBD3, the most highly charged β-defensin (charge of +11) has been demonstrated to be a neutral antagonist, through charge based interaction with melanocortin receptor 1 and 4 (82). In dogs, a three base pair deletion in the canine orthologue of HBD3 results in an increase in the level of expression, which then allows this peptide to promiscuously bind the melanocortin receptor 1 (MC1R)-resulting in dogs with black, rather than agouti, fur (83).…”
Section: Receptor Neutral Antagonismmentioning
confidence: 99%
“…Cachexia is invariably linked to immunosuppression. As strongly charged molecules, defensins might interact with MCR solely through electrostatic interactions explaining their neutral antagonist effect (Nix et al 2013, 2015). There is little doubt that these interactions play a role in determining melanocortin response on MC1R, as defensins seem to block agouti in live animals (Candille et al 2007, Kerns et al 2007).…”
Section: Pharmacological Complexities Of α-Msh Signalingmentioning
confidence: 99%
“…However, data are not as consistent for MC4R, and MC3R is yet to be tested as a potential defensin target. Electrostatic-based binding modalities open the possibility for additional undefined peptidic ligands to emerge as possible ‘modulators’ of AgRP and α-MSH signaling in energy balance (Nix et al 2015). …”
Section: Pharmacological Complexities Of α-Msh Signalingmentioning
confidence: 99%
“…Melanocortin receptor pharmacology is complex, with two antagonists/inverse agonists (AgRP and agouti signaling peptide) and MSH ligands that exhibit varying degrees of receptor specificity (Figure 1B ; Cone et al, 1996 ). Other ligands and cell-surface proteins have been identified that regulate melanocortin signaling (e.g., melanocortin receptor accessory proteins 1 and 2, mahogany, mahoganoid, attractin-like protein, syndecans, ion channels and defensins) (Kaelin et al, 2008 ; Nix et al, 2013 , 2015 ; Anderson et al, 2016 ).…”
Section: An Overview Of the Central Nervous Melanocortin Systemmentioning
confidence: 99%